Digital sustainability communication in tourism - Flávio Borges Tiago; Artur Gil; Sara Stemberger; Teresa Borges-Tiago (Journal of Innovation & Knowledge (JIK), 2021)
The relevance of sustainable tourism is unquestionable. Tourism and hospitality firms worldwide are moving toward more sustainable product offerings. However, not all firms communicate their achievements and commitments in this area. This study assesses the sustainable digital communication of small and medium accommodation firms and relates that information to the sophistication of their online presence. For this purpose, data were retrieved from the websites of 759 accommodation firms located in the Azores (S\~ao Miguel Island), classified as a sustainable island destination. The results indicate that international accreditations are less commonly adopted than local accreditations and that smaller firms tend to value eco-labeling when promoting their offers online. It is also noticed that sustainable achievements are highlighted on more sophisticated websites. This is one of the first studies to explore online sustainability communication; more specifically, the link with website sophistication among tourism SMEs. It is hoped that this study will stimulate further research on communication and SME practices on tourism sustainability and improve policy efforts to promote wider adoption of sound practices.
Keywords: Z1; Z3; 650; Accommodation; Digital communication; Eco-labels; SME; Sustainable tourism; Website sophistication